CONTRIBUTION TO THE INVESTIGATION OF THE INFLUENCE OF TIRE NON-UNIFORMITY ON THE LATERAL TIRE CHARACTERISTICS - Žunjić, Milena; Demić, Miroslav; Rakićević, Branislav; Đorđević, Branislav (Journal of Applied Engineering Science, 2022)
Tire models are widely used in research in the field of vehicle dynamics and noise, and especially in the simulation of their movement under the action of forces and moments. In general case, we distinguish theoretical models defined on the basis of tire construction and empirical or semi-empirical models based on experimental tests. In addition, a combination of these two types of models can also produce tire models. In practice, there is a very wide range of mathematical tire models defined using finite element analysis, by approximation of polynomials of different degrees, by approximation of magic formula, etc. In this paper, an attempt is made to calculate non-stationary lateral characteristics of tires on the basis of experimental stationary lateral characteristics, using two-parameter higher level polynomials. This polynomials define the tire lateral characteristics, and take into account their non-uniformity. More specifically, the lateral characteristics are approximated as a function of the dynamic change of the slip angle, radial load due to tire non-uniformity and time.
Keywords: tires, models, lateral characteristics, 3D Fourier transformation